Alternative Determination of TPS Waste Management in Karangkates Village, Malang Regency Based on Local Wisdom - Nenny Roostrianawaty; Anis Artiyani; Candra Dwi Ratna; Reza Firman Ardiansyah; Nikki Reallyari; Marell Sudarman Santoso; Devina Oktavia; Diva Tri Fena (Formosa Journal of Applied Sciences, 2023)
Karangkates Village has problems in handling waste where as the population increases, the amount of waste generated increases. The Temporary Waste Storage Site (TPS) is no longer able to accommodate the rate of waste generation, so a waste management plan at the TPS is needed to help with existing waste handling problems. There are 2 alternative waste management approaches that are expected to be used as a solution to solving the waste problem, namely TPST and TPS3R. The concept of integrated waste management includes the activities of reducing, sorting, collecting, utilizing, transporting and processing. TPS 3R is carried out by processing wet and dry waste which aims to reduce the amount of waste generation. Waste management at TPS in general as an effort to empower the community requires special stages that lead to local wisdom. Efforts to reduce household waste Waste disposed of in excavations based on its type, namely organic and inorganic waste. Organic waste is left alone because over time it will decompose along with the soil and make it fertile, while inorganic waste is burned because it cannot decompose naturally. This is pro-environmental behavior. With increasing globalization and lack of land in the region, waste is picked up by garbage collectors and dumped at the final collection point. Environmental knowledge, local wisdom, and environmental attitudes are classified as very significant and make a real contribution to people's behavior in managing waste in housing.